N Nagari or Village Government Communication Strategies in Improving Rural Economic Development - Sabri, Sabri; Suhatman, Suhatman; Nasfi, Nasfi (IJOSMAS, 2021)
Regional autonomy will affect the economic development of rural communities, but if it is managed and delivered with communication and communication strategies, it will reach the message recipient, moreover this message will be received by rural communities, who have different perceptions and ways of processing messages. So the communication strategy applies the concept of communication, communication models and understands the scope of the communication. To achieve economic development for rural communities, the nagari or village government has a role and carries out a mass communication process to message recipients. The method in research is used normatively and empirically, with the aim of research to find out the strategy of the nagari or village government in managing nagari or village assets in order to improve the economy of rural communities and the benefits of this research have the advantage in solving pihat communication problems related to nagari or village in solving problems in the village, although there have been many other studies, there are still differences in terms of nagari governance or village communities.